Pengaruh Osmopriming Benih terhadap Perkecambahan dan Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) pada Cekaman Kekeringan - Nikita Besty Novanursandy; Diah Rachmawati (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Cayenne pepper (Capsicum frutescens L.) is a commodity that often experiences price fluctuations due to a decrease in the supply of cayenne pepper amidst a large market demand. One of the factors causing the decrease in the supply of cayenne pepper is the environmental conditions that experience drought stress during the dry season. Osmopriming of seeds is one method that can be used to overcome drought stress. This study aims to determine the effect of osmopriming seeds using PEG 6000 on the germination and growth of cayenne pepper plants on drought stress. This study was experimental using a completely randomized design, with 2 treatment factors and 3 replications. The first factor was the application of priming at three concentration levels: P0 (0% PEG), P1 (12.5% PEG), and P2 (25% PEG). The second factor was drought stress treatment which consisted of 3 levels, namely: K1 (100% field capacity), K2 (75% field capacity), and K3 (50% field capacity). Data analysis used univariate analysis of variance and followed by DMRT (Duncan's Multiple Range Test) advanced testing with α = 0.05. The results showed that the application of 25% PEG priming gave the most optimal results on the performance of germination and growth of cayenne pepper plants, such as plant height, root length, root fresh weight, shoot fresh weight, root dry weight, and shoot fresh weight.